Pengaruh Kombinasi Urutan Daun Stephania hernandifolia Walp. dan Penambahan Volume Air terhadap Kualitas dan Sineresis Cincau selama Penyimpanan - Ningtyas, Putri Zulaida; Prihastanti, Erma; Saptiningsih, Endang (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Cincau is a kind of jelly food that is included in functional foods. Stephania hernandifolia Walp. is one type of plants that can be used in cincau production. Cincau was produced from squeezing of S. hernandifolia leaf which has been mixed with water. The sequence of leaves when picking it and the addition of water volume can affect the quality of cincau. This research aims to know the effect of S. hernandifolia combination sequence leaves and addition of water volume in cincau production towards the coagulation time, fiber content, vitamin C content andÂ chlorophyll content, and also to know the syneresis and shrinkage of cincau mass in the different storage time. The research was done at Laboratory of Biology Structure and Function of Plant, Biology Department â€“ Faculty of Mathematics and natural sciences, Diponegoro University in 2011. The design that is used in this research is Completely Randomized Design (CRD) pattern 2 x 3 factorial. Data were analysed by Analysis of Variance (ANOVA) and then continued by Duncan test with 95% level of significance. The result showed that the interaction of the combination sequence leaves and addition of water volume has no effect on coagulation time, chlorophyll, fiber, and cincau vitamin C. The storage time affects the syneresis and shrinkage of cincau mass. Key word : Stephania hernandifolia Walp., cincau, syneresis, shrinkage of mass.